Low 25-hydroxyvitamin D level increases carotid intima-media thickness in elderly women - Imran, Yudhisman; Aswar, Andini; Rachmiyani, Irmiya; Adriani, Donna (Faculty of Medicine, Trisakti University, 2019)
BackgroundCerebrovascular disease occurs due to atherosclerosis of the carotid artery triggered by endothelial dysfunction, which can be assessed by measuring the carotid intima-media thickness (CIMT). There are several risk factors contributing to endothelial dysfunction, such as 25-hydroxyvitamin D [25(OH)D] deficiency. A number of research studies have shown variable results on the relationship between 25(OH)D deficiency and endothelial dysfunction. The objective of the present study was to determine the relationship between 25(OH)D and CIMT in elderly women.METHODS A cross-sectional study was conducted involving 45 elderly women aged ≥60 years. The inclusion criteria were: able to communicate well and able to walk actively without any help. The exclusion criteria were: not having diabetes mellitus, stroke, heart disease, kidney disease, not consuming vitamin D or medicines containing corticosteroids, and not using hormone replacement therapy. Laboratory examination was conducted for fasting blood sugar, lipid profile, and 25(OH)D. CIMT was measured using carotid Doppler ultrasonography at the left carotid artery. Simple linear regression analysis was used to analyze the data.RESULTSMean 25(OH)D level was 11.753 ± 4.027 ng/mL, and mean CIMT 0.61 ± 0.10 mm. Simple regression analysis showed a significant relationship between 25(OH)D level and CIMT (β=-0.001; 95% C.I.=-0.020-0.003; p=0.009).CONCLUSION Our data suggest an inverse association between 25(OH)D level and CIMT in elderly women. This study supports the protective role of vitamin D against subclinical atherosclerosis in elderly women.